PENGARUH FAKTOR-FAKTOR GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERBANKAN DI INDONESIA (Studi Pada Perusahaan Perbankan Yang Terdaftar Di BEI Tahun 2010-2013) (Students' Journal of Accounting and Banking, 2015)
This research aims to analysis influence of factors good corporate governance of the performance of banks in Indonesia listed on the Indonesia stock exchange. The population is banking all companies listed on the indonesia stock exchange. The techniques that we use is the sampling purposive. The analysis used in this research are multiple linear regression model. The result showed that the coefficients determination in this research is the value of adjusted R square worth 27%. While for F-test statistic shows that between a board of directors, the board of commissioners, the board of independent commissioner, audit committee and institutional ownership in together influential against return on assets. And the results of the testing of hypotheses partial evaluation shows that there is a positive influence a board of directors, the board of commissioners independent committee and the audit for return on assets. As for the board of commissioners and ownership show an influence institutional negative on return on assets.Keywords: The Board of Directors, Board of Commissioners, The Board of Commissioners Independent, Audit Committee, Institutional Ownership and Return On Asset